2018
DOI: 10.1021/acs.joc.8b02878
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Diverse Collections of Benzoxazepine and Indolopyrazine Fused to Heterocyclic Systems

Abstract: The development of efficient and modular synthetic methods for the synthesis of diverse collection of privileged substructures needed for a drug design and discovery campaign is highly desirable. Benzoxazepine and indolopyrazine ring systems form the core structures of distinct members of biologically significant molecules. Several members of these families have gained attention due to their broad biological activities, which depend on the type of ring-fusion and peripheral substitution patterns. Despite the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The recent decade has witnessed an upsurge in the employment of diversity-oriented synthesis strategies for the de novo construction of first-in-class small molecules needed for phenotypic screening campaigns [ 22 , 23 , 24 ]. Among the structural options, the benzopyrane scaffold is a privileged architecture representing the core structure of a wide range of biologically appealing molecules [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The recent decade has witnessed an upsurge in the employment of diversity-oriented synthesis strategies for the de novo construction of first-in-class small molecules needed for phenotypic screening campaigns [ 22 , 23 , 24 ]. Among the structural options, the benzopyrane scaffold is a privileged architecture representing the core structure of a wide range of biologically appealing molecules [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of abundant Lewis acid sites (Zr 4 + ) in the highly ordered crystalline structure of the UiO-66 could be the main reason for its outstanding catalytic activity. [41] After optimizing the solvent and temperature effects and demonstrating the significance of UiO-66 compared with the other catalysts, the model reaction was carried out using various amounts of the catalyst (Table 1, entries [14][15][16]. It was observed that a decrease in the amount of the catalyst from 0.01 g to 0.006 g did not change the reaction yield, where 0.006 g was chosen as the optimal catalyst loading ( Table 1, entry 15).…”
Section: Resultsmentioning
confidence: 99%
“…[15] Representative examples of some biologically important benzoxazepines and benzodiazepines are illustrated in Scheme 1. Although many advances have been developed for the synthesis of benzoxazepines and benzodiazepines over the last decade, [16][17][18][19][20][21][22][23][24][25][26] the fascinating wide range of biological activities of these therapeutic agents have continuously encouraged scientists to design novel synthetic protocols with operationally simple procedure, inexpensive catalysts, and high yielding.…”
Section: Introductionmentioning
confidence: 99%
“…In another important utilization of these pluripotent building blocks, our group have recently disclosed ad iversity-oriented synthesis of distinctly functionalized benzoxazepine scaffolds of types 42 and 44.I nt his process, various aldehydes suitably poised with Michael acceptors, fore xample, 36,p henylene diamines (41)a nd 2-aminobenzamides (43), were utilized. [31] The cascadec ombines condensation, Mannish, oxidation, and aza-Michael addition reactions and was promoted by scandium tri-flate in acetonitrile. In this approach, the authors werea ble to construct ap ilot library of more than 30 members in af amily of underdeveloped chemical space (Scheme 10).…”
Section: Synthesis Of Benzoxepines and Benzoxazepinesmentioning
confidence: 99%